Carbon-nitride 2D nanostructures: thermal conductivity and interfacial thermal conductance with the silica substrate. Issue 5 (18th January 2019) - Rajabpour, Ali; Bazrafshan, Saeed; Volz, Sebastian
Abstract : The rate of heat dissipation from a carbon-nitride 2D nanostructure depends on the interfacial thermal conductance with its substrate. It was found that a structure with higher thermal conductivity, has a lower value of interfacial thermal conductance with the silica substrate. Abstract : The rate of heat dissipation from a 2D nanostructure strongly depends on the interfacial thermal conductance with its substrate. In this paper, the interfacial thermal conductance of carbon-nitride 2D nanostructures (C3 N, C2 N, C3 N4 's) with silica substrates was investigated using transient molecular dynamics simulations. It was found that a 2D nanostructure with higher thermal conductivity, has a lower value of interfacial thermal conductance with the silica substrate. The thermal conductivity of suspended carbon-nitride 2D nanostructures was also calculated using the Green–Kubo formalism and compared with that of graphene as a reference structure. It was found that the thermal conductivities of C3 N, C2 N, C3 N4 (s-triazine) and C3 N4 (tri-triazine) are respectively 62%, 4%, 4% and 2% that of graphene; while their interfacial thermal conductances with silica are 113%, 171%, 212% and 188% that of graphene. These different behaviors of the thermal conductivity and the interfacial thermal conductance with the substrate may be important in the thermal management of carbon-nitride 2D nanostructures in nanoelectronics.